Huge intermediate-grade myofibroblastic sarcoma in the retroperitoneum revealed by 18F-FDG PET/CT: a case report - Li, Xiaotian; Mei, Tengyue; Wang, Pan; Cai, Jiong; Hu, Xianwen (Frontiers in Medicine, 2024)
Myofibroblastic sarcoma (MS) is a relatively rare malignant bone and soft tissue tumor, which originates from myofibroblasts, with some characteristics of both smooth muscle cells and fibroblasts. It can develop in individuals at any age and can affect various regions, especially the head and neck; however, it is rarely reported retroperitoneally. Generally, this type of sarcoma is considered a low-grade malignancy, and cases classified as moderate and high-grade malignancy are rare. In this study, we describe a case of intermediate-grade myofibroblastic sarcoma (IGMS) originating from the retroperitoneum, which was confirmed through pathological diagnosis. The 18F-fluorodeoxyglucose (18F-FDG) positron emission tomography (PET)/computed tomography (CT) scan revealed a large, borderless mass located retroperitoneally with a significantly increased 18F-FDG uptake, accompanied by adjacent visceral and soft tissue infiltration and peripheral lymph node metastasis. The patient received chemotherapy for 3 weeks; however, the tumor did not shrink significantly. Therefore, the patient discontinued the treatment. After 5 months, his condition gradually deteriorated, which eventually led to death. Through this case report, the diagnosis and treatment of moderate malignant retroperitoneal myofibroblastoma were discussed, aiming to increase clinicians' understanding of this disease.